A Study of Morphological Variations of Carotid Bifurcation and Branching Pattern of External Carotid Artery in Adult Nigerian Cadavers - , I. U. Gwunireama, I. F. Bob-Manuel, G. U. Collins (Archives of Current Research International, 2023)
Background: Understanding the morphological differences in the branching pattern of carotid vessels has played a significant role in successful surgical operations around the neck region. This study aimed at evaluating the morphological variants of the external carotid artery (ECA) in relation to its carotid bifurcation (CB) and its branches. Methods: After obtaining twenty-five (25) hemi-necks and later dissected, 25 ECAs were examined (13 right and 12 left). The patterning of the superficial branches and CB from common carotid artery were photographed and later analyzed in terms of variations of origin. Results: CB appeared as V-shaped in 24 cases (96%). Superior thyroid artery (STA) originated majorly from both the ECA (40.91%) and from the CB (36.36%). The percentage distributions of occurrence of arterial branch origins from ECA in both hemi-neck sides are as follows; ascending pharyngeal (85.71%), lingual (84%), facial (88%) and occipital (95%). Conclusion: In adult Nigerian cadavers, the V-shaped carotid bifurcation pattern is more common and the CB was more prevalent at the level of the upper border of thyroid cartilage. Higher numbers of origins were observed more in STA compared to other superficial branches of ECA.